(1)由an=8-2n,
得a1=6,d=an-an-1=8-2n-[8-2(n-1)]=-2(n≥2).
再由an=8-2n≥0,得n≤4.
∴等差数列{an}的前4项大于等于0,从第5项起小于0.
则当n≤4时,数列{|an|}的前n项和
Tn=na1+
=6n+n(n?1)d 2
=7n-n2;n(n?1)(?2) 2
当n>4时,数列{|an|}的前n项和
Tn=|a1|+|a2|+…+|an|
=a1+a2+a3+a4-a5-a6-…-an
=-(a1+a2+…+an)+2(a1+a2+a3+a4)
=?
+2[4×6+6×(?2)]=n2-7n+24.(6+8?2n)?n 2
综上,Tn=
7n?n2 (n≤4)
n2?7n+24 (n>4)
(2)由bn=2an=28?2n,得bn+1=28?2n+1.
=
bn+1
bn?1+1
=
28?2n+1
28?2(n?1)+1
(n≥2).
28?2n+1
210?2n+1
当n=2时,
=
28?2n+1
210?2n+1
.17 65
当n=3时,
=
28?2n+1
210?2n+1
.5 17
∴数列{bn+1}不是等比数列.